Effectiveness of a Pharmacist-Directed Tdap Immunization Program for a University Campus - BreAnna R. Meinzer; Michael J. Rush; Karen L. Kier; Amy M. Fanous; Colin S. Frank (Ohio Journal of Public Health, 2019)
Background/Objectives: Despite a slight increase in Tdap immunization rates, the total numbers are still low among adults. The purpose of this study is to determine the impact of a pharmacist-directed immunization program. The primary objective was to assess the increase in vaccination rates among the subjects indicated to receive the Tdap vaccine. The secondary objective was to assess changes in pre and post vaccine knowledge scores. Methods: Employees enrolled in the pharmacist-directed employee wellness clinic on a university campus in Ohio were screened for Tdap vaccination at the annual employee health fair during Fall of 2016. Results were cross-referenced with the state vaccination database. Subjects were recruited via email to an educational program. Indicated patients were asked to schedule an appointment with a pharmacist. Assessment data on the educational program was collected before the presentation and after the appointment when the vaccine was administered. The efficacy endpoint for the primary objective was a 20% increase in baseline vaccination rates. Results: Of the 198 subjects recruited, a total of 54 received Tdap vaccination. The baseline vaccination rate of the study population was 37.4% and increased by 27.2% after the intervention to a total vaccination rate of 64.6% (p< 0.001). Six knowledge assessments were utilized for the secondary objective; however, these results did not show significance. Conclusions: A pharmacist-directed Tdap immunization program is effective at increasing vaccination rates. Even though the change in education assessment data proved more observational, the education provided will empower subjects to make informed healthcare decisions.
Keywords: Pharmacists; vaccination; diptheria-tetanus-aceliuar pertussis vaccines; population health